(untitled) (World Economics and Finance Bulletin, 2022)
This article reveals the theoretical provisions for improving the level of innovative expansion of the organization based on the rationalization of the device for managing its innovative potential. The model of hierarchical organizational management of innovative development is shown. The proposed model of hierarchical organizational management makes it possible to reveal the unused intellectual potential of the personnel, avoiding the limitation of the management process and contributing to the achievement of the necessary systematization and consistency of control actions.